(untitled) - Spellman, Frank R. (Boca Raton, 2008)
Water and wastewater treatment plant operators must have a breadth of knowledge that encompasses more than scientific theory. With two new chapters and more than 300 new practice scenarios, this second edition continues to offer a complete resource exclusively for water and wastewater plant operators. It is a thorough compilation of water science, treatment information, process control procedures, problem-solving techniques, safety and health information, and administrative and technological trends. The manual examines numerous real-world operating scenarios, including the intake of raw sewage and the treatment of water via residual management. Each scenario includes a comprehensive problem-solving practice set.
Nước cấp, nước thải kỹ nghệ
Keywords: Water treatment plants,Sewage disposal plants,Water,Xử lý nước cây trồng; Purification